2023
DOI: 10.1111/jdv.19725
|View full text |Cite
|
Sign up to set email alerts
|

Improved clinical effectiveness of adalimumab when initiated with clindamycin and rifampicin in hidradenitis suppurativa

P. Aarts,
J. C. van Huijstee,
H. H. van der Zee
et al.

Abstract: BackgroundAdalimumab monotherapy for hidradenitis suppurativa (HS) is often insufficient with a maximum clinical efficacy of 60% in Hidradenitis Suppurativa Clinical Response (HiSCR) and limited effect on draining tunnels. Data suggest that adalimumab therapy could be improved by concomitant antibiotics.ObjectiveTo compare the clinical effectiveness of adalimumab with clindamycin and rifampicin versus adalimumab monotherapy after 12 weeks.MethodsThis retrospective study included patients who started adalimumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Results of the study were excellent, the authors report that combination therapy demonstrated greater clinical efficacy expressed in median improvement in IHS4 (−20 vs. −9, p < 0.001), IHS4-55 (74% vs. 36%, p = 0.002), median reduction in draining tunnel (−4 vs. −2, p < 0.001) and pain response (47% vs. 27%, p = 0.02), 1 so adalimumab initiated with clindamycin and rifampicin shows greater clinical effectiveness than adalimumab monotherapy. 1 We completely agree that adalimumab monotherapy for HS may be insufficient showing a maximum clinical efficacy of 60% in Hidradenitis Suppurativa Clinical Response (HiSCR) and limited effect on draining tunnels. 2,3 The guidelines 4 on antibiotic therapy for HS cited by Aarts et al state that the combination of rifampin and clindamycin is planned for moderate-severe forms for up to 12 weeks; however, the also recommend tetracyclines for 12 weeks for mild-moderate forms.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Results of the study were excellent, the authors report that combination therapy demonstrated greater clinical efficacy expressed in median improvement in IHS4 (−20 vs. −9, p < 0.001), IHS4-55 (74% vs. 36%, p = 0.002), median reduction in draining tunnel (−4 vs. −2, p < 0.001) and pain response (47% vs. 27%, p = 0.02), 1 so adalimumab initiated with clindamycin and rifampicin shows greater clinical effectiveness than adalimumab monotherapy. 1 We completely agree that adalimumab monotherapy for HS may be insufficient showing a maximum clinical efficacy of 60% in Hidradenitis Suppurativa Clinical Response (HiSCR) and limited effect on draining tunnels. 2,3 The guidelines 4 on antibiotic therapy for HS cited by Aarts et al state that the combination of rifampin and clindamycin is planned for moderate-severe forms for up to 12 weeks; however, the also recommend tetracyclines for 12 weeks for mild-moderate forms.…”
mentioning
confidence: 64%
“…
Dear Editor, We have read with great interest the article recently published on your Journal entitled "Improved clinical effectiveness of adalimumab when initiated with clindamycin and rifampicin in hidradenitis suppurativa" by Aarts et al 1 The authors conducted a retrospective study included 61 hidradenitis suppurativa (HS) patients who started adalimumab with additional clindamycin and rifampicin (n = 31) and patients (n = 31) treated with adalimumab monotherapy, matched on sex and refined Hurley score. The primary outcome measure was the difference in change in the International Hidradenitis Suppurativa Severity Score System (IHS4) at 12 weeks.
…”
mentioning
confidence: 99%